DIVULGAÇÃO CIENTÍFICA NA ESFERA MIDIÁTICA - Grillo, Sheila Vieira de Camargo (Intercâmbio, 2010)
Based on Bakhtin’s and Bourdieu’s notions of social spheres, we investigate the media discourse coercions on scientific vulgarization.